“Era with war of talent”: Impact of HRM practices on employee retention among Malaysian SMEs - Ooi, Joe Yee (2023)
Small and Medium-sized businesses (SMEs) contribute significantly to the Malaysian economy and can be classified based on their size in terms of sales turnover, number of employees, and sector. In the era of globalization, the situation of talent shortage has resulted in a fierce “talent war” among companies of all sizes and industries worldwide, and the Malaysian SMEs often find themselves at a disadvantage compared to larger companies. Human Resource Management (HRM) practices play a critical role in every SMEs as the issues of employee retention has been a mission of companies to keep continuity with better goal attainment and capture market share. This is because losing even one key employee could have extensive consequences and may even jeopardize the companies’ efforts to attain its objectives. Human Capital Theory and Ability, Motivation, Opportunity (AMO) Theory are useful in predicting the impacts of HRM practices that are applied in companies from employees’ perspectives. In this study, HRM practices of training, remuneration and reward, performance appraisal, employee empowerment, career development, and working condition were investigated among the Malaysian SMEs on the impact to employee retention. A sample of 250 responses were collected from the Malaysian SME full-time employees using convenience sampling method of self-administered survey approach. Using Pearson’s correlation analysis, the findings indicated that all HRM practices have a very significant positive relationship on employee retention in Malaysian SMEs. This study also discussed on the implications of the study, as well as the limitations and recommendations that could be well-enhanced for future researchers.